2020
DOI: 10.1038/s41416-020-01092-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlative serum biomarker analyses in the phase 2 trial of lenvatinib-plus-everolimus in patients with metastatic renal cell carcinoma

Abstract: Background No biomarkers have been established to predict treatment efficacy in renal cell carcinoma (RCC). In an exploratory retrospective analysis of a Phase 2 study, we constructed composite biomarker scores (CBSs) to predict progression-free survival (PFS) and overall survival (OS) in patients with metastatic RCC randomised to receive lenvatinib-plus-everolimus. Methods Of 40 biomarkers tested, the 5 most strongly associated with PFS (HGF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Evaluation of interaction terms for predictive biomarkers requires anywhere from 4 to 16 times the sample size needed for testing main effects, and one approach to address this is to raise the cutoff for the p -value when considering interactions [ 26 ]. Clear predictive biomarkers for treatment of RCC have not been reported [ 27 ], and some studies have taken the approach of using multiple biomarkers to calculate a composite biomarker score for benefit, including for everolimus versus sunitinib [ 19 ] and more recently, for lenvatinib plus everolimus versus everolimus alone [ 28 ]. Additional studies are needed to identify predictive biomarkers in advanced RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of interaction terms for predictive biomarkers requires anywhere from 4 to 16 times the sample size needed for testing main effects, and one approach to address this is to raise the cutoff for the p -value when considering interactions [ 26 ]. Clear predictive biomarkers for treatment of RCC have not been reported [ 27 ], and some studies have taken the approach of using multiple biomarkers to calculate a composite biomarker score for benefit, including for everolimus versus sunitinib [ 19 ] and more recently, for lenvatinib plus everolimus versus everolimus alone [ 28 ]. Additional studies are needed to identify predictive biomarkers in advanced RCC.…”
Section: Discussionmentioning
confidence: 99%
“…We could not identify markers for non-Responders, but many such transcripts that changed in Responders included an increase in IL-18 mRNA that was also detectable in serum protein levels. A differential increase in serum IL-18 associated with longer OS was also reported for lenvatinib plus everolimus, 38 but a decrease was reported for atezolizumab. 37 IL-18 synergizes with IL-12 to increase transcript level for IFNG, 39 and IFNG is among the 565 genes expressed at higher levels in the CheckMate 009 Responders at day 28 ( online supplemental table S5 ).…”
Section: Discussionmentioning
confidence: 79%
“… 37 IL-18 synergizes with IL-12 to increase transcript level for IFNG, 39 and IFNG is among the 565 genes expressed at higher levels in the CheckMate 009 Responders at day 28 ( online supplemental table S5 ). The conflicting observations for association between serum IL-18 levels and OS with nivolumab, 25 lenvatinib plus everolimus, 38 or atezolizumab 37 may reflect the importance of assay timing relative to therapeutic response. In sum, IL-18 is a nivolumab mechanistic marker that potentially allows monitoring of response in the periphery.…”
Section: Discussionmentioning
confidence: 99%
“…However, the differences did not reach statistical significance. Recently, Lee et al also found the blood levels of angiopoietin-2 to have predictive and prognostic properties in their biomarker analysis [ 28 ]. In another study comparing everolimus alone vs. lenvatinib alone vs. everolimus plus lenvatinib, angiogenesis- and inflammatory-related proteins, including angiopoietin-2 and IL-18BP, were also associated with the PFS or OS [ 29 ].…”
Section: Discussionmentioning
confidence: 99%